Answer:
[tex]36x^6y^3[/tex]
Step-by-step explanation:
The problem needs application of law of indices
[tex]1. (xy)^m = x^my^m[/tex]
This means common power for terms can be applied to each term individually.
[tex]x^a x^b = x^(a+b)\\[/tex]
Separate power for the terms having same base can be added together.
_______________________________________________________
we will be using these law of indices in the problem
[tex](3xy)^2x^4y \\=> 3^2x^2y^2x^4y[/tex]
applied the first rule of indices as mentioned above
[tex]3^2x^2y^2x^4y\\=>9*x^(2+4)4y^(2+1)\\=>9*4x^6y^3\\=>36x^6y^3[/tex]
applied the second rule of indices as mentioned above
Thus, simplified form of (3xy)^2x^4y is [tex]36x^6y^3[/tex].